2022
DOI: 10.3390/jcm11061611
|View full text |Cite
|
Sign up to set email alerts
|

Delay Discounting in Gambling Disorder: Implications in Treatment Outcome

Abstract: Impulsive choice, measured by delay discounting (DD) tasks, has been shown in patients with gambling disorders (GD). However, the impact of DD and treatment outcome has been scarcely explored in GD patients. The aims of this study were: (1) to examine the baseline association between DD and clinical variables in GD patients depending on their age and gambling preferences (strategic vs. non-strategic); and (2) to estimate the predictive role of DD on poorer outcomes of cognitive-behavioral therapy (CBT) when co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…In studies of GD, some authors have found no differences in dropouts when gambling preferences are taken into account [36]. However, other studies have linked delay discounting to dropout in individuals with GD whose preferences are non-strategic or mixed types of gambling [27]. In another study, gambling on machines has been associated with pre-treatment dropout, while sports betting has been linked with dropout during GD treatment [56].…”
Section: Addiction-related Features Disorder Severity and Dropoutmentioning
confidence: 97%
See 2 more Smart Citations
“…In studies of GD, some authors have found no differences in dropouts when gambling preferences are taken into account [36]. However, other studies have linked delay discounting to dropout in individuals with GD whose preferences are non-strategic or mixed types of gambling [27]. In another study, gambling on machines has been associated with pre-treatment dropout, while sports betting has been linked with dropout during GD treatment [56].…”
Section: Addiction-related Features Disorder Severity and Dropoutmentioning
confidence: 97%
“…On the other hand, others noted that younger participants with GD exhibited higher dropout [26,27], and attended fewer treatment sessions before abandoning interventions [27]. Young age has even been considered in different studies as a main predictor of dropout from GD treatment [22,28].…”
Section: Sociodemographic Features and Dropoutmentioning
confidence: 99%
See 1 more Smart Citation
“…Impulsivity and emotional instability are broad transdiagnostic constructs that have been described in association with different mental disorders (Amlung et al., 2017; Griffin et al., 2018; Lee et al., 2019; Munguía, Jiménez‐Murcia, et al., 2021) and physical conditions (Jorge et al., 2022; Testa et al., 2021). Impulsivity includes behavioural and cognitive facets characterised by the tendency to act quickly without prior reflection, possibly leading to undesirable consequences (Evenden, 1999) such as harmful or suicidal behaviours (Valenciano‐Mendoza et al., 2021), adverse emotional consequences (e.g., more depression, anxiety; Aldao et al., 2016), as well as poorer treatment adherence (Mallorquí‐Bagué et al., 2021; Mena‐Moreno et al., 2022) and outcomes (Vintró‐Alcaraz et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Greater DD is associated with an array of maladaptive behaviors (Levitt et al, 2023) including substance use (Amlung et al, 2017; Gowin et al, 2019; Strickland et al, 2021; Weinsztok et al, 2021) in both clinical (Baker et al, 2003) and nonclinical populations (Kollins, 2003). Importantly, greater DD has been shown to identify those at risk for developing a SUD as well as drug-use severity (Audrain-McGovern et al, 2009; Bickel et al, 2014; Martínez-Loredo et al, 2018) and predict poorer treatment outcomes and greater relapse risk following initial treatment success (González-Roz et al, 2019; Mena-Moreno et al, 2022; Stanger et al, 2012; Washio et al, 2011; Yoon et al, 2007).…”
mentioning
confidence: 99%